Metabolomics and multivariate data analysis - Khatib, Alfi (2020)
Metabolomics is a holistic analytical approach which aims to analyze whole metabolites in a given set of samples. This technique is becoming trending nowadays due to its accuracy and robustness. It has been applied in many fields including pharmacognosy and pharmacology. The best statistical method that is fit to this approach is multivariate data analysis which covering multiple variables of both dependent and independent parameters. This statistical analysis reduces a type 1 error due to multiple variables by producing latent variable. This presentation describes some examples of metabolomics application in herbal science in conjunction with pharmacology as well as brief explanation of introduction to multivariate data analysis.